НОВЫЕ ПРАВОЗАЩИТНЫЕ ИНИЦИАТИВЫ ГРАЖДАНСКОГО ОБЩЕСТВА РЕСПУБЛИКИ МОЛДОВА - Сосна, Борис Ильич (SUPREMANCE OF LAW, 2018)
Everyone is entitled to all the rights and freedoms. The relevance of the article is due to the fact that protection of fundamental human rights and freedoms, today, is emerging from the jurisdiction of states, it ceases to be exclusively an internal matter of each state and becomes an object of protection of the entire world community. This article was prepared by the Institute for Democracy (Moldova). This article is funded by the European Union (European Unions Confidence Building Measures Programme - СВМIV). Opinions expressed in the article do not necessarily represent those of the European Union.
Keywords: EU; Civil society of the Republic of Moldova; NGOs; Confidence Building Measures